Determinant factor affected the presence of Aedes sp. in a customary village - Pascawati, Nur Alvira; Satoto, Tri Baskoro Tunggul (International Journal of Public Health Science (IJPHS), 2023)
Vector surveillance and control are the only reliable means for the prevention and control of dengue fever and dengue hemorrhagic fever, such as in Customary Village environments. Indonesia is an archipelagic country that has many Customary Villages, so the variables that affect the breeding of dengue vectors are numerous and complex. This study identifies potential vector breeding places and environmental factors for the presence of Aedes sp. in Customary Villages. A study with a cross-sectional design was conducted in the Segenter Customary Villages, West Nusa Tenggara, Indonesia. Simple and multiple logistic regression analysis to identify risk factors associated with the presence of Aedes larvae. The results showed that the entomological index was in the high category and at risk as a potential breeding place for the Aedes sp. The determinant factor that affects the presence of dengue vectors is the traditional type of house (p-value=0.005; RP=2.138). This factor is strengthened by the 70-90% humidity (p-value= 0.009; RP=1.764), 25-30 oC house temperatures (p-value=0.011; RP=1.650), and mixed type house (p-value=0.067; RP=1.413). These findings contribute to the development of an early warning system regarding the potential spread of Aedes vector-borne diseases, increase awareness, promote and prevention of dengue fever (DF), and its vectors to healthy tourism in Indonesia.